2017
DOI: 10.1097/bsd.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Extracavitary Approach Versus Posterior Extensive Circumferential Decompression in the Treatment of Complicated Thoracic and Lumbar Tuberculous Spondylitis

Abstract: Both procedures attained good results for maintained deformity correction, bony fusion, spinal cord decompression, and neurological improvement in complicated tuberculous spondylitis. However, PECD may be superior to LEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Twenty-five studies comparing the anterior, posterior, or anterior combined with posterior approach in treating spinal tuberculosis in the thoracic and lumbar regions were identified. 11 35 Table 1 summarizes the characteristics of the included studies. Among the 25 studies, the anterior surgical approach mainly referred to anterior debridement, decompression, and bone grafting with different fixations in a one- or two-stage procedure; the posterior surgical approach mainly referred to posterior debridement, decompression, and bone grafting with different fixations in a one- or two-stage procedure; and the anterior combined with posterior surgical approach referred to anterior and posterior (or posterior and anterior) debridement, decompression, and bone grafting with different fixations in a one- or two-stage procedure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-five studies comparing the anterior, posterior, or anterior combined with posterior approach in treating spinal tuberculosis in the thoracic and lumbar regions were identified. 11 35 Table 1 summarizes the characteristics of the included studies. Among the 25 studies, the anterior surgical approach mainly referred to anterior debridement, decompression, and bone grafting with different fixations in a one- or two-stage procedure; the posterior surgical approach mainly referred to posterior debridement, decompression, and bone grafting with different fixations in a one- or two-stage procedure; and the anterior combined with posterior surgical approach referred to anterior and posterior (or posterior and anterior) debridement, decompression, and bone grafting with different fixations in a one- or two-stage procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies 11 , 12 , 14 , 16 18 , 20 , 22 26 , 28 35 reported the preoperative kyphosis angle and correction of the kyphosis angle in patients with thoracic and lumbar spinal tuberculosis ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably due to the neurological consequences leading to disruption of functional abilities, emphasizing the indication for surgery. Studies that examined surgery techniques recorded a considerable number of patients with compromised preoperative neurological status [2,[7][8][9][10][13][14][15]23,25]. On the other hand, fewer studies evaluated functional outcomes from conservative management among individuals with spinal tuberculosis; however, those who underwent conservative management were less likely to have neurological deficits to begin with [16,17].…”
Section: Discussionmentioning
confidence: 99%